The South-American distribution and southernmost record of Biomphalaria peregrina-A potential intermediate host of schistosomiasis - Rumi Macchi Zubiaurre, Alejandra (2017)
Schistosomiasis remains a major parasitic disease, endemic in large parts of South America. Five neotropical species of Biomphalaria have been found to act as intermediate hosts of Schistosoma mansoni in natural populations, while others have been shown to be susceptible in experimental infections, although not found infected in the field. Among these potential intermediate hosts, Biomphalaria peregrina represents the most widespread species in South America, with confirmed occurrence records from Venezuela to northern Patagonia. In this study, we report the southernmost record for the species at the Pinturas River, in southern Patagonia, which finding implies a southward reassessment of the limit for the known species of this genus. The identities of the individuals from this population were confirmed through morphological examination, and by means of two mitochondrial genes, cytochrome oxidase subunit I (COI) and 16S-rRNA. With both markers, phylogenetic analyses were conducted in order to compare the genetic background of individuals from the Pinturas River with previously genetically characterized strains of B. peregrina from various South- American locations. In addition, we produced a potential distribution model of B. peregrina in South America and identified the environmental variables that best predict that distribution. The model was estimated through a maximum entropy algorithm and run with occurrence points obtained from several sources, including the scientific literature and international databases, along with climatic and hydrographic variables. Different phylogenetic analyses with either the COI or 16S-rRNA sequences did not conflict, but rather gave very similar topological organizations. Two major groups were identified, with sequences from the Pinturas River grouping together with haplotypes from subtropical and temperate regions. The model developed had a satisfactory performance for the study area. We observed that the areas with higher habitat suitability were found to be mainly linked to subtropical and temperate regions of South America between 15° and 45° south latitude, with different moderate- and lowsuitability areas outside this range. We also identified the coldest temperatures as the main predictors of the potential distribution of this snail. Susceptibility surveys would be required to evaluate if southern populations of B. peregrina still retain their potential as intermediate hosts of S. mansoni.